2022
DOI: 10.1101/2022.05.25.22275603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The prevalence of SARS-CoV-2 infection and other public health outcomes during the BA.2/BA.2.12.1 surge, New York City, April-May 2022

Abstract: ImportanceRoutine case surveillance data for SARS-CoV-2 are incomplete, biased, missing key variables of interest, and may be unreliable for both timely surge detection and understanding the burden of infection.ObjectiveTo determine the prevalence of SARS-CoV-2 infection during the Omicron BA.2/BA.2.12.1 surge in relation to official case counts, and to assess the epidemiology of infection and uptake of SARS-CoV-2 antivirals.DesignCross-sectional survey of a representative sample of New York City (NYC) adult r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
4
9
0
Order By: Relevance
“…This study fills a gap in the literature by examining the association between testing groups and vaccination choices by utilizing vaccine registries (in contrast to self-reporting) to obtain vaccine histories for all three testing groups. Overall trend in home-testing vs laboratory-based testing as well as race, ethnicity and vaccination status differences between testing groups observed in this study is consistent with that reported in survey-based studies ( 9 , 12 , 13 , 17 ) and could be compared with each other. This study demonstrates that certain populations are more likely to use only home tests.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study fills a gap in the literature by examining the association between testing groups and vaccination choices by utilizing vaccine registries (in contrast to self-reporting) to obtain vaccine histories for all three testing groups. Overall trend in home-testing vs laboratory-based testing as well as race, ethnicity and vaccination status differences between testing groups observed in this study is consistent with that reported in survey-based studies ( 9 , 12 , 13 , 17 ) and could be compared with each other. This study demonstrates that certain populations are more likely to use only home tests.…”
Section: Discussionsupporting
confidence: 89%
“…Official reports and other analyses were primarily based on laboratory-based testing, as home tests were not typically included in data systems that track COVID-19 cases and rates. Consequently, there was a dearth of information on home test usage and users; the research available on this topic is limited to surveys that have a higher risk of response bias and were conducted on adults ( 12 , 13 ). Given this fact, there is a critical need to better understand individuals, including children, who use and report home tests, as well as the trends in home testing.…”
Section: Introductionmentioning
confidence: 99%
“…The strengths of this study include the analysis of tests during the Omicron period with widespread home testing coverage and population-based large sample sizes using case investigation data collected by trained interviewers, as opposed to survey data impacted by response bias. However, testing trends as well as demographic (age, race) and vaccination status observed were consistent with survey-based studies (9, 12, 13, 17) and were able to validate each other. This study demonstrated that certain populations are more likely to use home tests only.…”
Section: Discussionsupporting
confidence: 80%
“…Official reporting, as well as other analytics, are primarily based on laboratory-based testing, as home tests are not typically reported to data systems tracking COVID-19 case volume and rates. Consequently, there is a dearth of information on home test usage and users; studies available are very few, survey-based with an associated response bias and are on adults (12, 13). Given this scenario, there is a critical need to better understand the individuals, including children, using and reporting home tests, as well as trends in home tests.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to prior findings using the same methodology 17,18 , we estimated a higher prevalence of SARS-CoV-2 infection among those who were vaccinated and boosted compared with those who were fully vaccinated but not boosted and those who were unvaccinated. Since vaccines and boosters provide limited protection against infection with omicron variants compared with prior strains 19 , these differences are likely due to differences in SARS-CoV-2 exposures and health behaviors between the two groups.…”
Section: Discussionsupporting
confidence: 78%